AKTIVITAS DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN PERTUMBUHAN DAN PERKEMBANGAN DENGAN METODE PRAKTIKUM - Hasmiati Hasmiati; Jamilah Jamilah; Muhammad Khalifah Mustami (Jurnal Biotek, 2017)
One effective method of learning science used is a lab / experimental. Practicum is not necessarily using sophisticated tools and materials and expensive, but can be done using simple tools and materials that are easily found around us. The purpose of this study was to determine the activity and results of class VIII student of SMP Negeri 7 Alla Enrekang in the subject matter of growth and development with practical methods utilize coconut water as a source of plant nutrients. This research includes studies Pre Experiment Design research design One-Shot Case Study. The population in this study were all students of class VIII SMPN 7 Alla school year 2015/2016, which consists of five classes with the number of students 153 people. Determination of the sample using purposive sampling sample obtained one sample class is class VIIIe by the number of learners 29. The research instrument used is the observation sheet student learning activities and tests in the form of multiple choice questions. Data analysis technique used is descriptive analysis of statistical data. The results of the research and analysis of the data shows that for the learning activities of students categorized as very high 80% and 20% for the high category while for the learning outcomes of students categorized as very high 41% and 59% higher category.